Factors affecting perception of laypeople and dental professionals toward different smile esthetics - Johnson Hsin-Chung Cheng; Yuan-Che Hsu; Tracy Yi-Hsuan Lee; Rou-Wei Li (Elsevier, 2023)
Abstract Background: /purpose: Several factors such as identity, income, and age potentially associated with smile perceptions. This study aimed to identify the factors affecting the smile esthetic perception in different identities (layperson, general dentist and orthodontist) and to detect the extent of their association with smile perception. Materials and methods: Extraoral photographs in frontal, lateral, and three-quarter views were shot and adjusted on Adobe Photoshop into 95 smile photographs with different smile patterns. Based on these photographs, the investigators were asked to fill the online questionnaire. Pearson chi-square test and logistic regression were used for statistical analyses. Results: Identity, gender, age, and treatment experience were noted to affect smile esthetic perception. In addition, the perception of smile esthetics was significantly different among frontal, lateral, and three-quarters views regarding the arc ratio, most posterior teeth exposure, upper teeth exposure, and lower teeth exposure. Conclusion: Identity, gender, age, and treatment experience influence the smile esthetics perception, with a significant difference in the results of the esthetic perception based on the 3 smile views. Of all demographic factors, identity had a strong relation to the perception of smile attractiveness. Nevertheless, additional studies are needed to realize how the demographic factors influence people's perception of smile esthetics, particularly in the three-quarter and lateral views.